Hb S-São Paulo: A new sickling hemoglobin with stable polymers and decreased oxygen affinity - Jorge, Susan E. D. C. (2012)
Hb S-São Paulo (SP) [HBB:c.20A > T p.Glu6Val; c.196A > G p.Lys65Glu] is a new double-mutant hemoglobin that was found in heterozygosis in an 18-month-old Brazilian male with moderate anemia. It behaves like Hb S in acid electrophoresis, isoelectric focusing and solubility testing but shows different behavior in alkaline electrophoresis, cation-exchange HPLC and RP-HPLC. The variant is slightly unstable, showed reduced oxygen affinity and also appeared to form polymers more stable than the Hb S. Molecular dynamics simulation suggests that the polymerization is favored by interfacial electrostatic interactions. This provides a plausible explanation for some of the reported experimental observations